5-Fluorouracil upregulates cell surface B7-H1 (PD-L1) expression in gastrointestinal cancers. Issue 1 (December 2016) - Van Der Kraak, Lauren; Goel, Gaurav; Ramanan, Krishnaveni; Kaltenmeier, Christof; Zhang, Lin; Normolle, Daniel; Freeman, Gordon; Tang, Daolin; Nason, Katie; Davison, Jon; Luketich, James; Dhupar, Rajeev; et al.
Abstract Background Resistance to chemotherapy is a major obstacle in the effective treatment of cancer patients. B7-homolog 1, also known as programmed death ligand-1 (PD-L1), is an immunoregulatory protein that is overexpressed in several human cancers. Interaction of B7-H1 with programmed death 1 (PD-1) prevents T-cell activation and proliferation, sequestering the T-cell receptor from the cell membrane, inducing T-cell apoptosis, thereby leading to cancer immunoresistance. B7-H1 upregulation contributes to chemoresistance in several types of cancer, but little is known with respect to changes associated with 5-fluorouracil (5-FU) or gastrointestinal cancers. Methods HCT 116 p53+/+, HCT 116 p53−/− colorectal cancer (CRC) and OE33 esophageal adenocarcinoma (EAC) cells were treated with increasing doses of 5-FU (0.5 uM, 5 uM, 50 uM, 500 uM) or interferon gamma (IFN-γ, 10 ng/mL) in culture for 24 h and B7-H1 expression was quantified using flow cytometry and western blot analysis. We also evaluated B7-H1 expression, by immunohistochemistry, in tissue collected prior to and following neoadjuvant therapy in 10 EAC patients. Results B7-H1 expression in human HCT 116 p53+/+ and HCT 116 p53−/− CRC cells lines, while low at baseline, can be induced by treatment with 5-FU. OE33 baseline B7-H1 expression exceeded CRC cell maximal expression and could be further increased in a dose dependent manner following 5-FU treatment in the absence of immune cells. We further demonstrate tumor B7-H1 expression in esophageal adenocarcinoma patient-derived pre-treatment biopsies. While B7-H1 expression was not enhanced in post-treatment esophagectomy specimens, this may be due to the limits of immunohistochemical quantification. Conclusions B7-H1/PD-L1 expression can be increased following treatment with 5-FU in gastrointestinal cancer cell lines, suggesting alternative mechanisms to classic immune-mediated upregulation. This suggests that combining 5-FU treatment with PD-1/B7-H1 blockade may improve treatment in patients with gastrointestinal adenocarcinoma.